The Effectiveness of English in Supporting Communication with Customers to Provide the Best Service in the World of Work - Ahmad, Ahmad; Sari, Ni Kadek Wahyuni Merta; Damayanti, Sri; Pranata, Andi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine the description of workers' ability to speak English, English is needed to communicate via online media/internet both with fellow actors and with consumers consisting of domestic consumers and tourists. The total sample technique used in this research was 70 people. The description of the characteristics of MSME actors consists of age, education, length of business, and media ownership, while the characteristics of MSMEs are presented based on micro, small and medium business scale. English language skills are measured based on the ability to read, understand and interpret messages on social media. Based on the formulation of research objectives and the results of data analysis tests, it can be concluded that the description of the characteristics of MSME actors mostly includes those of productive age (80%), most of the respondents are male (40%), the education of MSME actors is dominated by undergraduate graduates (60%), and has Most have more than 5 years of experience and most have more than 1(77.14%) media experience. The characteristics of business scale include small scale (50%), only 1.43% of medium scale ones were in the research sample. The description of the English language skills of MSME players is quite good with an average score of 3.32, while the ability to use media has a better average score than English language skills, namely 3.42. The results of the correlational analysis show that there is a very real positive relationship between English language ability and media use ability, which is expressed by an r value of 0.993, meaning that the higher the English language ability, the higher the media use ability.